2021
DOI: 10.4103/njm.njm_42_21
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of COVID-19 and Practice of Preventive Measures among Adult Residents During the Ease of Lockdown in Nigeria

Abstract: Background: The governments of many countries have taken steps to avert the spread of COVID 19. The gradual relaxation of the lockdown in Nigeria might be counter-productive if not properly managed. The best means to reduce and stop transmission is for the public to be adequately informed about the disease and its preventive measures. This research assessed the knowledge of COVID-19 and practice of preventive measures along with its predictors among Nigerian residents during the ease of the lockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…fearful than the males and the rapid rise of COVID-19 with the attendant fear might be responsible for this higher proportion of female participants observed in this study. This was obtained in similar crosssectional studies in Egypt24 , Iran26 , Saudi Arabia 27 , Cameroon28 , Ethiopia29 and Nigeria30 where the female participants are also more than the males.…”
supporting
confidence: 65%
“…fearful than the males and the rapid rise of COVID-19 with the attendant fear might be responsible for this higher proportion of female participants observed in this study. This was obtained in similar crosssectional studies in Egypt24 , Iran26 , Saudi Arabia 27 , Cameroon28 , Ethiopia29 and Nigeria30 where the female participants are also more than the males.…”
supporting
confidence: 65%
“…This is lower than that reported by a study done in Nigeria through social media that reported 67% of practice among their participants. 46 Another study done in the South-Eastern part of Nigeria reported a 53.6% overall good practice. 47 .…”
Section: Discussionmentioning
confidence: 96%